Pengelolaan Sampah Di Kota Tanggerang : Upaya Penerapan Kebijakan Publik - Faradila Ananda; Rahmawati; Agung Satrio Wicaksono (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The purpose of this study is based on the formulation of the problem that has been determined, namely to find out how to implement the Waste Management Policy in Cipondoh District, Tangerang City. This study uses a qualitative research design with the intention of understanding and delving deeper into the Implementation of Waste Management Policy in Cipondoh, Tangerang City. The data collection technique in this study uses primary sources and secondary sources. The tools used for data collection consist of: interview guides. The results of the research on the implementation of the waste bank management policy in Cipondoh District, Tangerang City, which was analyzed using the policy implementation theory of George C. Edward III, showed that the implementation of the policy has shown significant efforts, but still faces various challenges in each of the main variables. Overall, the implementation of the waste bank management policy in Cipondoh District still requires strengthening in terms of public communication, human resource capacity, implementation incentives, and bureaucratic consistency. A more inclusive participatory approach and adaptive technical policies are needed to increase the effectiveness of community-based waste management through waste banks. With the strengthening of the four Edward III variables, it is hoped that the waste management policy can run more optimally and sustainably.